Reaction Mechanism for Selective Oxidation of Anethole to Anisaldehyde by Hydrogen Peroxide in Presence of Ferric Vanadate - Yao, Xingdong; Peng, Caihua; Shi, Zhanwang (Asian Journal of Chemistry, 2014)
The reaction mechanism and kinetics for the oxidation of anethole to anisaldehyde by H2O2 in the presence of ferric vanadate have been investigated. The results show it is a homogeneous system with vanadium oxodiperoxo ion as the actual oxidant. The reaction follows the pseudo-first order rate equation. Free radical reaction mechanism has been verified by DPPH. A plausible reaction mechanism has been proposed based on the experimental results.